(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
Verga wrote the novel Una peccatrice in Catania in 1864, but he published it in 1866 after a two-year long revision and moreover, after his first permanence in Florence. These aspects made the novel a good proof of young Verga’s linguistic and stylistic progress, although the author himself judged his novel as a «juvenile sin». Linguistic analysis of text’s variations reveals Verga’s attempt to distance himself from the language of his previous novels, characterized by weak linguistic competence, and to gain a style appropriate to describe middle-class and aristocracy. In general, lexical variations portray a research of an “average language”, balanced between two opposed tendencies: the register’s elevation and the research of a more fluent language. Moreover, Verga tries to distance himself from a dialect that was still too vivid in the text’s first version. Not all Verga’s attempts arrived to success, but the analysis of Una peccatrice’s variants shows an important moment of the author’s linguistic and stylistic research.